PRAKTIK GOOD ENVIRONMENTAL GOVERNANCE DAN SUSTAINABLE RURAL DEVELOPMENT STUDI KASUS: DESA REJOSARI, KECAMATAN BANTUR, KABUPATEN MALANG - Resya Famelasari; Maria Chiquita (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2018)
This study aims to analyze the regulation of village regulations and environmental programs with the community to overcome the environmental problems of drought and topography of the region in Rejosari Village, Bantur District, Malang Regency. The conceptual framework used in the research is Good Environmental Governance and Sustainable Rural development. The research methodology is descriptive qualitative by implementing in-depth interview. This study concludes that in some programs reforestation is reinforced by Perdes No.10 of 2016, Perdes No.12 of 2016 and other environmental programs have implemented Good Environmental Governance values through several indicators of policy content, policy process and policy context. One of Porang Cultivation program is also an innovation of food crop agriculture product which can be categorized as a realization program of effort to realize Sustainable Rural Development in Rejosari Village area.Keywords: Village regulations, Environmental Programs, Good Environmental Governance, Sustainable Rural Development